2018
DOI: 10.1111/jocs.13567
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve-in-valve implantation for early failure of sutureless aortic bioprosthesis

Abstract: We report a case of early failure of a Perceval sutureless aortic bioprosthesis (LivaNova, London, UK) which was treated with a transcatheter valve-in-valve implantation with an Edwards 3 bioprosthesis (Edwards Lifesciences, Irvine, CA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Dvir et al suggested that there is a greater risk of coronary obstruction in stentless valves, especially Sorin Freedom Solo valve, where the coronary obstruction occurs significantly more frequently than in the other stentless valves. Nevertheless, VIV TAVI has been successfully performed in sutureless valves . Although we did not use any form of coronary ostia protection during the procedure, no coronary obstruction was observed in our series regardless of the previously implanted bioprosthesis.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Dvir et al suggested that there is a greater risk of coronary obstruction in stentless valves, especially Sorin Freedom Solo valve, where the coronary obstruction occurs significantly more frequently than in the other stentless valves. Nevertheless, VIV TAVI has been successfully performed in sutureless valves . Although we did not use any form of coronary ostia protection during the procedure, no coronary obstruction was observed in our series regardless of the previously implanted bioprosthesis.…”
Section: Discussionmentioning
confidence: 75%
“…Nevertheless, VIV TAVI has been successfully performed in sutureless valves. 18 Although we did not use any form of coronary ostia protection during the procedure, no coronary obstruction was observed in our series regardless of the previously implanted bioprosthesis.…”
Section: Long-term Follow-upmentioning
confidence: 69%
“…The most common described mechanism of failure was so-called "stent creep" wherein the valve framework bends inward thereby deforming the valve leading to an increased aortic valvular gradient which ultimately leads to valve failure [10]. There are a number of reports of ViV-TAVR repair of SPV failure due to stent creep [7][8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing use of percutaneous cardiac valve placement either as primary therapy or for failing bioprosthetic valves . Percutaneous valves also have been implanted in adults with previous congenital cardiac surgical repairs .…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing use of percutaneous cardiac valve placement either as primary therapy or for failing bioprosthetic valves. 1 Percutaneous valves also have been implanted in adults with previous congenital cardiac surgical repairs. 2 A challenging patient subset are those with tricuspid or mitral annuloplasty rings, as these have very small "landing zones" for the percutaneous valves.…”
Section: Introductionmentioning
confidence: 99%